Growth, recovery and bioaccumulation of alfalfa (Medicago sativa) and spinach (Spinacia oleracea) exposed to cyanotoxins in agricultural environments - Nezat, Caryn Janel, author; Omur-Ozbek, Pinar, advisor; Peebles, Christie, committee member; Bailey, Ryan, committee member (Colorado State University. Libraries, 2020)
Harmful algal blooms (HABs) are a growing concern for surface water resources around the globe. With increasing pressure on our limited fresh water resources due to climate change, the risk of contamination from HABs and the cyanobacterial toxins that accompany blooms, exacerbates the problem. Adverse health effects from cyanotoxin exposure has been documented in human and animal mortality and morbidity cases worldwide. Nationally, the presence and severity of HABs has prompted multiple cyanotoxins, including cylindrospermopsin (CYN) and microcystins (MCLR), to be listed on the USEPA Drinking Water Contaminant Candidate List-4 (CCL4) requiring many public systems to monitor for cyanotoxin presence. Recognizing this risk, the World Health Organization (WHO) has long established guidelines to acceptable levels in surface waters based on exposure pathways and use. Further concerns have arisen as our understanding about cyanotoxins has been expanded by research. The purpose of this experiment was to determine 1) effects of toxin exposure during germination, 2) the effects of CYN and MCLR on agricultural crops exposed to toxins during vegetative and mature growth stages, 3) crops ability to recover from toxin exposure and 4) to quantify amount of cyanotoxin accumulated within crop tissue after exposure to cyanotoxins. Germination results indicated exposure to CYN and MCLR did not decrease the rate of germination of alfalfa or spinach. Further, alfalfa and spinach had increased primary root growth for seeds exposed to cyanotoxins. During early vegetative exposure, spinach showed increased biomass and larger leaf area when exposed to MCLR and CYN. After a recovery period spinach plants exposed to CYN showed increased biomass compared to controls. Alfalfa plants exposed to MCLR in vegetative stages had significantly more biomass when compared to controls and this trend was observed after the recovery period. Results of alfalfa exposed during mature growth stages to CYN and MCLR indicated it was more sensitive to CYN, however both toxin treatments resulted in increased biomass production. After one- and two-weeks of recovery the MCLR treated alfalfa biomass remained higher than controls. Bioaccumulation of CYN and MCLR was observed in alfalfa exposed early to the toxins and detectable levels were observed after the one-week recovery period. Spinach accumulated MCLR during early exposures and had detectable levels in the stems after one-month recovery. During mature exposure, alfalfa initially only had detectable levels of MCLR, which decreased over the recovery periods. However, the presence of CYN was not detected until one-week prior to the final toxin exposure. These findings support the growing concern that use of cyanotoxin contaminated irrigation water can be an additional exposure route for ingestion of toxins and increased risk of adverse health effects. Further studies into the subsurface fate of cyanotoxins will further increase the understanding of their bioavailability and persistence in soil.
Keywords: bioaccumulation; cylindrospermopsin; agriculture; microcystin; cyanotoxins